'He is just getting old, you know': the role of cultural and health beliefs in shaping the help-seeking process of family members caring for persons with dementia in Vietnam. Issue 7 (3rd October 2022) - Nguyen, Trang; Levkoff, Sue; Nguyen, Huong
ABSTRACT: Objectives: This study aims to examine the help-seeking process of family caregivers for persons with dementia (PWD) in Vietnam, and how health and cultural beliefs shape this process. Design: Twenty family caregivers of PWD at a geriatric hospital in Northern Vietnam were recruited. A total of 30 face-to-face, semi-structured interviews, including 10 follow-up interviews, were conducted. Structural coding was used first to guide data analysis through four structural codes consistent with the four stages of the help-seeking model: (1) disease and symptom experience; (2) explanatory models for symptom appraisal; (3) decision to seek help; and (4) contact with the sources of help. Then thematic coding was used for more detailed and data-driven initial codes to emerge from the data. Results: Cultural and health beliefs, particularly collectivist values, such as familism and filial piety, shaped each stage of Vietnamese family caregivers' help-seeking process. Caregivers experienced different PWD's symptoms and adopted a mixed explanatory model combining biomedical and folk beliefs to explain the causes of dementia. They highly valued independence, autonomy, devotion to their family, and self-sacrifice, making these values the driving force underlying their self-reliance regime in caregiving. Help-seeking was often delayed until caregivers considered the situation to be beyond their own capacity to manage independently. The family was always the primary informal source of support for caregivers, with additional help sought from friends, neighbors, and religious facilities. Health professionals, if available, were also an important formal source for medical advice. Conclusions: The results highlight the importance of culture and health beliefs in shaping caregivers' help-seeking process, and advocate the needs of service development targeting not only Vietnamese family caregivers for PWD, but also caregivers sharing similar collectivist culture in different areas. Interventions and services that are consistent with their values of self-sacrifice, devotion to family, autonomy, and self-reliance are much needed.